2022
DOI: 10.1002/acm2.13452
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning a secondary dose calculation software for a 0.35 T MR‐linac

Abstract: Secondary external dose calculations for a 0.35 T magnetic resonance image‐guided radiation therapy (MRgRT) are needed within the radiation oncology community to follow safety standards set forth within the field. We evaluate the commercially available software, RadCalc, in its ability to accurately perform monitor unit dose calculations within a magnetic field. We also evaluate the potential effects of a 0.35 T magnetic field upon point dose calculations. Monitor unit calculations were evaluated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…45,47,49 The 0.35 T MRIdian beam also characterized an asymmetry crossline profile. 61 A Monte Carlo simulation showed that the negative side…”
Section: Change To Beam Percentage Depth Dose (Pdd) and Dose Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…45,47,49 The 0.35 T MRIdian beam also characterized an asymmetry crossline profile. 61 A Monte Carlo simulation showed that the negative side…”
Section: Change To Beam Percentage Depth Dose (Pdd) and Dose Profilesmentioning
confidence: 99%
“…Lower magnetic field strength is expected to have reduced dose effects 45,47,49 . The 0.35 T MRIdian beam also characterized an asymmetry crossline profile 61 . A Monte Carlo simulation showed that the negative side of the crossline penumbra in the lung slab region was 3 mm larger than the inline penumbra 45 …”
Section: Interplay Between the Magnetic Field And Secondary Electronsmentioning
confidence: 99%
“…Since the 0.35 T ViewRay MRIdian MRL was first introduced in 2017, numerous papers have been published regarding MRL acceptance testing/commissioning and quality assurance (QA) [8] , [9] , [10] , [11] , [12] , [13] . Due to the presence of magnetic fields, the imaging QA of these MRL systems became critical to the accuracy of treatment delivery, such as MRI localization, voxel sizing, and distortion correction [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Price et al first commissioned commercial software RadCalc (LifeLine Software,Austin,TX,USA) to MRIdian system and investigated point dose analysis (with and without magnetic field) on the adaptive plans. 7 Wang et al developed an in-house Monte Carlo system built upon graphics processing unit (GPU)-accelerated dose planning method (gDPM) on the MRIdian system to validate adaptive plans with consideration of magnetic fields and achieved within 2.3 min on average for implementation in ART. 8 For the Unity, several studies explored the utility and performance of existing commercial software, such as with RadCalc 9 and MU2Net (DOSIsoft, France), 10 and the hybrid of in-house developed GPU-accelerated Monte Carlo-based dose verification module into a commercial software ArcherQA.…”
Section: Introductionmentioning
confidence: 99%
“…Price et al. first commissioned commercial software RadCalc (LifeLine Software, Austin, TX, USA) to MRIdian system and investigated point dose analysis (with and without magnetic field) on the adaptive plans 7 . Wang et al.…”
Section: Introductionmentioning
confidence: 99%